2004
DOI: 10.1111/j.1467-8624.2004.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linguistic Analysis of Vocabulary in Young Children: Spanish, Dutch, French, Hebrew, Italian, Korean, and American English

Abstract: The composition of young children's vocabularies in 7 contrasting linguistic communities was investigated. Mothers of 269 twenty-month-olds in Argentina, Belgium, France, Israel, Italy, the Republic of Korea, and the United States completed comparable vocabulary checklists for their children. In each language and vocabulary size grouping (except for children just learning to talk), children's vocabularies contained relatively greater proportions of nouns than other word classes. Each word class was consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
159
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(190 citation statements)
references
References 92 publications
17
159
1
3
Order By: Relevance
“…This result can be explained by alluding to the process of the acquisition of nouns. As previous research has shown (Gentner, 1981;Kim, McGregor and Thompson, 2000;Bornstein et al 2004;Gentner and Baroditsky, 2009), nouns are the first word class to be acquired because they are more transparent in their meaning, since they are used to label concrete objects. Indeed, the results of our study confirm the early acquisition of the meaning of nouns given the fact that the most frequent lexical errors in nouns are related to their form.…”
Section: Can Lexical Errors Inform About Word Class Acquisition In Thmentioning
confidence: 94%
See 1 more Smart Citation
“…This result can be explained by alluding to the process of the acquisition of nouns. As previous research has shown (Gentner, 1981;Kim, McGregor and Thompson, 2000;Bornstein et al 2004;Gentner and Baroditsky, 2009), nouns are the first word class to be acquired because they are more transparent in their meaning, since they are used to label concrete objects. Indeed, the results of our study confirm the early acquisition of the meaning of nouns given the fact that the most frequent lexical errors in nouns are related to their form.…”
Section: Can Lexical Errors Inform About Word Class Acquisition In Thmentioning
confidence: 94%
“…Traditionally, there is the firm belief that all types of words are not equally easy to acquire. This belief has its origin in the observation of native language acquisition (Caselli et al, 1995;Bornstein et al, 2004;Gentner and Baroditsky, 2009), where children seem to acquire nouns first, then verbs, and finally adjectives and adverbs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This noun bias has been well-documented in naturalistic studies of children learning their first language (e.g., Bornstein et al, 2004;Gentner, 1982) and even two languages simultaneously (Levey & Cruz, 2003), yet very few language studies have turned an eye toward the possibility of a noun bias among adult language learners. Findings from two studies suggest there could be a noun bias among adults just as among young children.…”
Section: A Potential For Noun Biasmentioning
confidence: 99%
“…Participants' average total foreign language proficiency was 8.49 (SD = 4.93). A number of participants reported various proficiencies in Spanish (26), French (9), Mandarin Chinese (6), Farsi (4), Hindi (4), Korean (4), Vietnamese (3), Polish (2), Italian (2), Polish (2), German (2), Urdu (2), and a number of other languages (reported once each: Canbrese, American Sign Language, Telegu, Amheric, Japanese, Persian, Punjabi, Tunisian Arabic, Arabic, Portuguese, and Nepali). Proficiency in any particular language was not analyzed as no special link was expected to exist between any of these and the target language, Hebrew.…”
Section: A Participantsmentioning
confidence: 99%
See 1 more Smart Citation